Enhancing Emergent Literacy Skills via Interactive Storytelling: Insights into Early Vocabulary Acquisition - Salma Dyday; Abdul Muiz Rouf; Cucu Sopiah (International Journal of Educational Qualitative Quantitative Research, 2026)
Traditional early literacy instruction often relies on decontextualized letter drilling, failing to foster integrated decoding and semantic comprehension. This study investigated the impact of a scaffolded interactive storytelling intervention on enhancing preschoolers' emergent literacy skills and early vocabulary acquisition. Grounded in a design-based practitioner inquiry framework, the intervention was implemented across two sequential phases with 13 preschoolers aged 5 to 6 years (M = 5.4, SD = 0.38). Data were gathered using a validated observation rubric (CVI = 0.92; k = 0.84) assessing grapheme-phoneme identification, word-picture association, and contextual word comprehension. Wilcoxon Signed-Rank Tests revealed a statistically significant improvement in overall emergent literacy performance from baseline (M = 1.92, SD = 0.81) to Phase II (M = 3.08, SD = 0.86; Z = -3.18, p < 0.001), yielding a large cumulative effect size (r = 0.88). Qualitative classroom observations confirmed a behavioral shift from passive memorization to active dialogic engagement, self-correction, and communicative confidence. Synthesizing Dual Coding Theory and Vygotsky’s Social Constructivism, these findings demonstrate that combining multimodal storybooks with dialogic questioning activates dual verbal and non-verbal cognitive channels, bridging orthographic decoding with semantic mapping. This study provides a theoretically sound, scalable model for reforming early childhood literacy curricula toward interactive, narrative-driven practices.